Analysis of the Intensity of Instagram Social Media Usage Regarding the Level of Social Ethics (Character) of Students at Madrasah Aliyah Laboratorium (MAL) UINSU Medan - Asri Karina Br. Sembiring; Junaidi Arsyad (FKIP - Universitas Riau, 2026)
In the current digital era, advancements in information and communication technology have transformed the paradigm of human social interaction. Social media stands out as a dominant technological product, with Instagram being one of the most popular platforms among adolescents. This study aims to examine the relationship between the intensity of Instagram usage and the level of social interaction ethics (character/conduct) among students at Madrasah Aliyah Laboratorium (MAL) UINSU. The study employs a quantitative descriptive approach using a correlational method. The total population consisted of 166 students, from which a sample of 49 students was selected using simple random sampling. The instruments used measured Instagram usage intensity and social interaction ethics. The results indicate that Instagram has a significant and strong influence on the students' social conduct and character at MAL UINSU. With a contribution value of 57.7%, it is evident that a substantial portion of the changes in students' ethical behavior is driven by how they use Instagram, while the remainder is influenced by external factors such as the family environment. This relationship is positive, implying that if Instagram usage is directed toward constructive and educational activities, the students' manners and social ethics at school are also likely to improve significantly.